Secondary Hip Fractures among Aging Adults with a Previous Hip Fracture History: Cumulative 50 Year Overview, Analysis, and Possible Antidote as Observed from 1974-2026 Data Sources - Ray Marks (Journal of Aging Research And Healthcare, 2026)
Hip fractures, which remain an immense public health concern, have been subject to study and prevention efforts for many decades, but with limited success in averting either incident, second or subsequent hip fractures, commonly attributed to a combination of age related proclivity to fall, low bone and muscle mass. This review examines second hip fracture incidence rates and determinants of this serious functionally debilitating injury as observed over time remains a current 2026 public health concern. It specifically explores if more preventive efforts are currently warranted in this regard, and in what respect, if indeed, more frail older adults are living longer, but may be in excessively poor health, fearful of moving or falling, malnourished, weak with poor balance, or depressed. Based on what is published, it is concluded 1) second hip fracture incidence rates remain considerable, especially among those who are frail with osteoporotic bone disease, poor vision, heart/or cognitive conditions, plus those with muscle deficits of the lower limb, live alone and have a falls history; 2) studies to identify possible mitigation approaches appear promising in this regard, along with more routine efforts to minimize falls risk and bone attrition.
Keywords: Hip Fractures